Preliminary results on the development of monoester type insulating oil from coconut oil. (August 2019) - Rajab, A; Putra, F E; Ramadhani, J S; Silitonga, M S I; Kurniawan, R; Qibran, K; Latif, M; Hamid, M I
Abstract: Vegetable oils, both in tri-ester and monoester forms have been attractive alternative substitutes for replacing mineral oil as the insulating liquid used in power transformer. An effort to develop a monoester type insulating oil derived from coconut oil has been conducted, and the preliminary results of the development are reported in this paper. Five different samples were prepared from methyl ester of coconut oil based on their melting point. The important properties of oil samples such as viscosity, water content, acidity, and density were tested, and are evaluated based on the standard specification of natural ester used for the transformer. Another fundamental property, i.e., oxidation stability was also tested and is evaluated by comparing the corresponding result of mineral oil. It is found that oil needs further treatment before being able to be used as insulating oil.